Adoption of computer-assisted audit tools and techniques (CAATTs): an exploratory study in audit firms - Ghani, Rusman; Ismail, Noor Azizi; Saidin, Siti Zabedah (2016)
This study focuses on exploring the adoption of Computer-Assisted Audit Tool and Techniques (CAATTs) among audit firms in Malaysia.This study also analyzed the reasons for the adoption of CAATTs by audit firms.This study used an interview method to explore what are the type of CAATTs adopted by the respondents of the audit firm.The findings reveal that there are some audit firms in practice adopted the CAATTs.The reasons are availability of financial resources, partners’ expertise and their clients’ nature of operation. The adoption of CAATTs is not compulsory by the law or standards however there is an encouragement from the authorities and accounting bodies for the practitioners to adopted CAATTs in their audit works.The findings should provide some inputs to the policy makers and practitioners into the current practice of auditing process and future regulations.The present study opens up opportunities and provide avenues for more in-depth research on the subject of CAATTs.